(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background:Tumor necrosis factor-? elaborated soon after myocardial ischemic injury. The intracellular adhesion molecule-1 is required for polymorphonuclear emigration, the primary cause of inflammatory tissue damage due to ischemia-reperfusion. Objective:Detect the serum level of tumor necrosis factor-? and to look for the percentage of expression of intracellular adhesion molecule-1 in atherosclerotic coronary heart disease. Methods: Fifty patients (40 males and 10 females) were enrolled in this study with age range (42-80) years, and fifteen, age and sex matched, apparently healthy individuals. The patients group was further classified into acute and chronic cases. Blood sample was taken from each subject and divided into 2 parts. One part used for lymphocyte separation by using immunocytochmistry to detect intracellular adhesion molecule-1 and the other one for serum separation by using ELISA technique to detect tumor necrosis alpha-?. Results:Significant difference in the concentrations of tumor necrosis factor-? was found between patients and control groups and it was elevated in acute cases compared to chronic cases. Similarly, intracellular adhesion molecule-1 was elevated in patients compared o control groups and more in acute than chronic cases. Conclusions: TNF-? is an important marker that acts on coronary arteries which may contribute to the development of congestive heart disease. Elevation of intracellular adhesion molecule-1 level correlates well with the development of acute events in the disease. Keywords:Atherosclerotic coronary heart disease, TNF-?, ICAM-1, ELISA, immunocytochemistry technique.